Предмет: Математика,
автор: grifer27547
помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
а (4; -7; -3)
b (-3; 6; 22)
3а = (3 × 4; 3 × (-7); 3 × (-3)) = (12; -21; -9)
- b = (-(-3); -6; -22) = (3; -6; -22)
3а - b = (12+3; -21-6; -9-22) = (15; -27; -31)
grifer27547:
если хоч можешь еще выполнить задачки у меня на профили еще есть по 50б
Похожие вопросы
Предмет: Физика,
автор: liapinamasha
Предмет: Литература,
автор: SonyPms
Предмет: Русский язык,
автор: Nagibator73
Предмет: Русский язык,
автор: ymka1311
Предмет: Русский язык,
автор: sjjssjsjnsjseoe